Using QuillBot Paraphraser in EFL Writing: The Effectiveness from Students' Perceptions - Dewi, Utami; Hasanah, Nur; Julaika, Siti; Sambas, Ela Carmelia Mukti (English Education : English Journal for Teaching and Learning, 2024)
The study investigates students' perceptions of Quillbot, an online tool for paraphrasing. The research involved 30 English undergraduate students in their fourth semester using descriptive quantitave. Data was collected through questionnaires. Results showed that 66% of students found Quillbot helpful in paraphrasing their writing, while 70% believed it enhanced vocabulary. 63% believed it improved sentence structure, and 60% felt it improved writing skills. 76% agreed that QuillBot helped choose appropriate language for paraphrasing, and 77% felt more confident in their writing. Overall, students had positive perceptions of Quillbot.